SOME CONSTRAINTS ON HIGH SCHOOL STUDENTS’ MATHEMATICS PERFORMANCE: AWI-ZONE & WEST- GOJAM, ETHIOPIA - Ahmed, Adem Mohammed (UPI Press, 2018)
This study was designed to examine the possible constraints that can affect high school students’ mathematics performance in five selected high schools in Awi-zone and west- Gojam. Observations and reports from examining bodies revealed that a high percentage of secondary school students continue to perform poorly in mathematics examinations. From a total of forty high schools, five were selected using simple random sampling technique. The respective sections were selected using purposive sampling techniques. Four sections were selected from each school. Then, 250 samples of students were employed using comprehensive sampling technique. To obtain data, questionnaire, classroom observation, and semi-structured interviews were used. 50 students from each school were selected using simple random sampling technique for the questionnaire. Similarly, three teachers from each of the sample school were selected using simple random sampling technique for the questionnaire, classroom observation and interview. The quantitative data were analyzed using one sample t-test whereas the qualitative one was analyzed using descriptive interpretations. The findings showed that students have laid claim on the problem of scoring passing mark as a result of poor mathematics performance. In addition, the result indicates that teachers possess the theories and their application of indirect instruction, organizing mathematics lessons, classroom management using assessment techniques. The findings also implied that there are opportunities to improve students’ performance in mathematics in the high schools to the expected level. Furthermore, the findings showed that paraphrasing math word problems can improve some students' performance. In relation to the findings of the study, recommendations are forwarded.